Lead and copper in hunted wild boars and radiographic evaluation of bullet fragmentation between ammunitions. Issue 3 (3rd July 2019) - Menozzi, Alessandro; Menotta, Simonetta; Fedrizzi, Giorgio; Lenti, Antonio; Cantoni, Anna Maria; Di Lecce, Rosanna; Gnudi, Giacomo; Pérez-López, Marcos; Bertini, Simone
ABSTRACT: The purpose of the present study was to evaluate the content of lead in carcasses of wild boars shot with lead bullets, in comparison with that of copper caused by lead-free ammunitions. Radiographic images of hunted boars were obtained in order to assess the degree of bullet fragmentation in the carcasses. Samples of meat were collected from different body areas at increasing distance from bullet trajectory, to be analysed by ICP-MS for lead and copper levels. In wild boars shot with lead ammunitions, a massive dispersion of bullet fragments and very high lead levels were detected. By contrast, in wild boars killed with copper ammunitions no radiographic signs of bullet fragmentation were observed. Copper ammunitions seem therefore a safer alternative to standard lead-core ones, due to their minimal fragmentation and the relatively low toxicity of this metal.